2010
DOI: 10.1080/07399330903359326
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Integration Theory: Implications of Supportive Communication for Breast Cancer Patients

Abstract: In this analysis, the authors apply Problematic Integration (PI) Theory to the way breast cancer patients engage in and receive support. The theory focuses on the relationship between expectations and desires, and enlightens cognitive and communicative responses to situations that involve tensions between their perceived likelihoods of occurrence and their perceived values. The relationship between PI Theory and its significance in treating and providing support for patients suffering from terminal illnesses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This study was able to demonstrate the negative effects of employees’ perceived uncertainty regarding ‘active coping’ with the illness and RTW having a back injury [31]. In their qualitative research of breast cancer patients, Repass and Matusitz [32] found uncertainty to be a central concept of the recovery phase. The women feared recurrence and being socially stigmatized.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This study was able to demonstrate the negative effects of employees’ perceived uncertainty regarding ‘active coping’ with the illness and RTW having a back injury [31]. In their qualitative research of breast cancer patients, Repass and Matusitz [32] found uncertainty to be a central concept of the recovery phase. The women feared recurrence and being socially stigmatized.…”
Section: Discussionmentioning
confidence: 95%
“…The women feared recurrence and being socially stigmatized. According to the authors, empowerment is needed by rebuilding healthy lifestyles through physical activity, to regain confidence through the realisation of the return to normality [32]. Women who have breast cancer seem to make a kind of transition from patient to survivor [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuity, availability, information and respect have been found to be essential aspects of professional support (Drageset et al, 2016). It is important to create supportive messages and support groups for cancer patients (Repass and Matusitz, 2010). Healthcare professionals should be sensitive.…”
Section: Experiences Of Support and Carementioning
confidence: 99%